Geography, livelihoods and rural poverty in Honduras: An empirical analysis using an asset-base approach - Jansen, Hans G. P.; Siegel, Paul B.; Alwang, Jeffrey; Pichón, Francisco (Universität Göttingen, 2005)
The overall objective of this paper is to develop an appropriate conceptual and analytical framework to better understand how prospects for growth and poverty reduction can be stimulated in rural Honduras. We employ complementary quantitative and qualitative methods of analysis, driven by an asset-base approach. Emphasis on assets is appropriate given high inequalities in the distribution of productive assets among households and geographical areas in Honduras. Such inequalities are likely to constrain how the poor share in the benefits of growth, even under appropriate policy regimes. We focus on household assets (broadly defined to include natural, physical, human, financial, social and locational assets) and their combinations necessary to take advantage of economic opportunities. We examine the relative contributions of these assets, and identify the combinations of productive, social, and location-specific assets that matter most to raise incomes and take advantage of prospects for poverty-reducing growth. Factor and cluster analysis techniques are used to identify and group different livelihood strategies; and econometric analysis is used to investigate the determinants of different livelihood strategies and the major factors that impact on income. Spatial analysis, community livelihood studies and project stocktakings are brought in to complement some of the more quantitative household survey data used. Our conclusions and recommendations are mainly focused on hillsides and hillside areas since the majority of the available data is for these areas. Our research resulted in five key findings with important strategic implications. First, there exists significant heterogeneity of rural areas in Honduras in terms of their asset endowments. But even areas with good economic potential often have persistent high rates of poverty because the poor lack the basic asset base to be able to capitalize on this potential. Second, poverty is widespread and deep in rural Honduras, particularly in hillside areas where most households have limited assets on which to base their livelihood strategies. High poverty density in hillside areas and the fact that some 80 percent of all rural poor are located in these areas, should make these areas a target of national rural poverty reduction strategies. Overlap between high poverty rates and high poverty densities in many hillside areas means that investments there should reach significant proportions of the country's rural poor with minimal leakages. Third, agriculture should form an integral part of the rural growth strategy in hillside areas, but its potential is limited. Over the past 25 years, agriculture has not been a strong engine of growth in rural Honduras. But high reliance of rural households on agricultural and related income means that any strategy targeted to these areas will have to build upon the economic base created by agriculture. Even though agriculture alone cannot solve the rural poverty problem, those remaining in the sector need to be more efficient, productive and competitive. Strategic actions and investments involving food security, security and access to land and forests, infrastructure provision, improved natural resource management, non-agricultural rural employment and migration are needed to achieve broad-based and sustainable agricultural growth and reduced rural poverty. Fourth, there is a need to move from geographically untargeted investments in single assets to a more integrated and geographically based approach of asset enhancement with proper complementarities. A multisectoral investment program is required to upgrade and improve access to household assets, with proper and more explicit complementarities. Finally, asset investment programs need to be adapted according to the specific needs of regions and households. While some household assets programs should be national in nature, others require more local adaptation and must be carried out in tandem, according to specific needs of regions and households. Investment strategies should be formulated on broad regional bases, but options within regions should be tailored to local asset bases.